Application unit for the administration of contrast gases for pulmonary magnetic resonance imaging: optimization of ventilation distribution for 3He‐MRI. Issue 3 (11th September 2014) - Güldner, M.; Becker, St.; Wolf, U.; Düber, C.; Friesenecker, A.; Gast, K. K.; Heil, W.; Hoffmann, C.; Karpuk, S.; Otten, E. W.; Rivoire, J.; Salhi, Z.; et al.
<x xml:space="preserve">Abstract</x> Purpose MRI of lung airspaces using gases with MR‐active nuclei (3He, 129Xe, and 19F) is an important area of research in pulmonary imaging. The volume‐controlled administration of gas mixtures is important for obtaining quantitative information from MR images. State‐of‐the‐art gas administration using plastic bags (PBs) does not allow for a precise determination of both the volume and timing of a 3He bolus. Methods A novel application unit (AU) was built according to the requirements of the German medical devices law. Integrated spirometers enable the monitoring of the inhaled gas flow. The device is particularly suited for hyperpolarized (HP) gases (e.g., storage and administration with minimal HP losses). The setup was tested in a clinical trial (n = 10 healthy volunteers) according to the German medicinal products law using static and dynamic ventilation HP‐3He MRI. Results The required specifications for the AU were successfully realized. Compared to PB‐administration, better reproducibility of gas intrapulmonary distribution was observed when using the AU for both static and dynamic ventilation imaging. Conclusion The new AU meets the special requirements for HP gases, which are storage and administration with minimal losses. Our data suggest that gas AU‐administration is superior to manual modes for determining the key parameters of dynamic ventilation measurements. Magn Reson Med 74:884–893, 2015. © 2014 Wiley Periodicals, Inc.